EXPERIMENTAL INVESTIGATION OF ALUMINUM-LIGHTWEIGHT CONCRETE COMPOSITE COLUMNS - Resan, Sa'ad Fahad (Basrah Journal for Engineering Sciences, 2014)
An experimental and theoretical study of light weight concrete filled aluminum tubes having circular hollow section is presented in this paper. The structural performance of columns was investigated using different light weight concrete fashions and compressive strengths. The column specimens were subjected to uniform axial compression with two different loading styles, in the first one (composite action); aluminum tube is utilized to be axially loaded as well as its confining function, and in the second loading style (confinement action), aluminum tube is utilized to confine concrete core only. The aluminum circular hollow sections have nominal proof stress, f 0.2 = 170 MPa. A grade of light weight expansion clay aggregate (LECA) is used to fabricate light weight concrete. The strengths, axial load- shortening displacement relationship, axial and lateral strains, and failure modes of columns are presented. The unfactored strengths predicted are found to be in a good agreement with the experimental values using the general design guidelines specified in the American specifications and Euro code.